Evaluación de las variables del desempeño cooperativo con enfoque en el buen vivir en Cotopaxi y Tungurahua. - Zambrano Cedeño, Maryury Margarita (2018)
In the present study, the variables of the cooperative performance of the savings and credit cooperatives of the provinces of Cotopaxi and Tungurahua were evaluated to determine their social impact and whether they tend to achieve the Good Living of their members and the community. For the development of this research, three phases were carried out, which were the identification of the cooperative performance variables, the structuring of the research tool and the application of the evaluation tools of the cooperative performance variables was carried out the activities proposed by the researchers, such as the compilation of bibliographic information based on the principles of cooperativism, Popular and Solidarity Economy, corporate responsibility and the principles of Good Living in order to sustain the research of the variables under study. Another of the activities developed was the interviews with the directors so that they could give the respective authorization to proceed with the development of the investigation, providing us with information on each one of the cooperatives as the total number of members and employees that make up these organizations, to then take a small sample of this population. Once our own population of members and employees was established, we proceeded to evaluate this population, as a process of research we tabulated the data obtained by respondents in this cooperative sector, which could be seen that these organizations are in the direction of compliance with the principles established by the ICA, Popular and Solidarity Economy, Corporate Social Responsibility and Good Living.